Drumheller Fountain showing (l to r) Old Meany Hall, the Science Hall (now Parrington Hall), and the Mines Building, ca. 1910
Frosh Pond was formerly known as Geyser Basin which was built for the AYPE. Today the pond contains Drumheller Fountain, built in 1961. Meany Hall was built in 1908 to serve as the auditorium for the Alaska-Yukon-Pacific Exposition. It was demolished in 1965 after suffering extensive damage in an earthquake. The building to the right was planned to be the Mines Building in preliminary plans for the AYPE but was actually called the Oriental Building during the Exposition. It was torn down in 1920. Caption on image: Freshman Basin Filed in: UW - Panoramas (#250)